PENCARIAN PASAL PADA KITAB UNDANG-UNDANG HUKUM PIDANA (KUHP) BERDASARKAN KASUS MENGGUNAKAN METODE COSINE SIMILARITY DAN LATENT SEMANTIC INDEXING (LSI) - Setyoko Yudho Baskoro; Achmad Ridok; Muhammad Tanzil Furqon (Journal of Environmental Engineering and Sustainable Technology, 2015)
Indonesia is a country of law. As law states, Indonesian have regulations that govern the relationship between the communities, one of them is criminal law. Set of rules of criminal law is written in the Kitab Undang-undang Hukum Pidana (KUHP), which contains hundreds of clause which regulate the relationship between the community based on values, norms, and specific rules that focuses on the interests of the public. In this paper, information retrieval used to search the clause of the KUHP based on a description of the crime, using Latent Semantic Indexing (LSI). LSI adopts techniques in mathematical dimension reduction process Singular Value Decomposition (SVD). This system use 60 clause as training data, and 6 query or crime description as test data. In each of the data clause of the KUHP contained data such as clause number, clause, and the clause contents. The system will calculate and determine the relevant clause is based on  query or  description of the crimes that has been entered. Cosine similarity used to calculate the similarity or proximity clause KUHP with query. The performance of the system is shown by the test results of Mean Average Precision (MAP) value at each k-rank is 5, 10, 20, 30, 40, 50, and 59, with the highest performance is in k-rank 40 with MAP 0.8944.